MODERN TEACHING TOOLS USED IN TEACHING PLANT PHYSIOLOGY - Arzimurodova , Muqaddas (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This methodology is designed for effective use of virtual technologies in biology teaching, focusing on a practical approach. These methods aim to create interactive and experiential opportunities for students, help them visualize and better understand biological processes, and ease the learning experience. The goal is to create interactive and virtual learning opportunities in biology education, inspire students to study biological processes, and make learning easy, engaging, and experiential through virtual technologies.